Quantum Computing Using Optics - Milburn, Gerard J.; White, Andrew G. (Computational Complexity, 2011)
Glossary Definition of the Subject Introduction Quantum Computation with Single Photons Conditional Optical Two-Qubit Gates Cluster State Methods Experimental Implementations Reprise: Single Photon States Future Directions Bibliography